Identifikasi dan Usulan Menangani Waste pada Proyek Mesin Selectifier dengan Pendekatan Lean Project Management Di PT. Z - Firmansyah, Abdullah; Momon, Ade (Fakultas Teknik Universitas Tulang Bawang, 2024)
The delay of a project can occur due to poor planning of its necessary resources, causing waste or waste. The purpose of this research is to find out the waste and its factors that can potentially occur in the selectifier machine project and know the viable solution to choose to deal with the waste. Then careful planning is required by applying the Lean Project Management methodology, where waste and harm can be found using scoring matrices and fishbone diagramming tools. Based on the analysis results in the selectifier machine project at PT. Z, the potential waste appears, namely waste waiting, defects and overprocessing. Waste and its potential causes are materials or components that are late dating, workers waiting for certain information, machines or tools supporting machine manufacturing are damaged, manufacturing process is not suitable for SOP, materials or components of poor quality, less scrupulous workers, poor working techniques. And according to the evaluation matrix, the best solution obtained is to perform other tasks that do not involve doing material work or using components that have not yet arrived on site, and buying back better materials from vendors. Keywords : Evaluation Matrix, Fishbone Diagram, Lean Project Management, Waste